The Penetration of 4.0 Industry Revolution Through Strengthening Human Resources Related to The Right to Work for Humanity - jandiman bernando pasaribu (CV. Strata Persada Academia, 2023)
The aim of this research is to assess the politics of employment law related to the right to work and the urgency of whether or not changes to Law Number 13 of 2003 are necessary to move towards the era of Industrial Revolution 4.0. This research is normative legal research with a statutory and conceptual approach. First, the right to work for every citizen aims for humanity as mandated by Article 27, paragraph (2) of the 1945 Constitution. Second, formal education and job training for workers are very important in facing the era of revolution 4.0 as strengthening human resources in the workplace. There is a need to change labor law, including regarding the regulation of job training, which is like two coins. Thus, efforts to face the era of Industrial Revolution 4.0 do not abandon the sense of humanity as part of the identity or identity of the Indonesian nation in the Preamble to the 1945 Constitution towards the life of Indonesian people towards goodness and the mandate in the 1945 Constitution regarding the right to work for everyone.